Evaluating the Resistance Performance of the VAEPC and the PAFRC Composites against a Low-Velocity Impact in Varying Temperature - Gwang-Hee Heo; Jong-Gun Park; Chung-Gil Kim (Advances in Civil Engineering)
This paper aims to evaluate the resistance performance of the vinyl acetate ethylene polymer cement (VAEPC) composite and the polyvinyl alcohol fiber-reinforced cement (PAFRC) composite against a low-velocity impact in varying temperature. Their impact resistance performances are analyzed and compared with plain mortar after 28 days of age. Low-velocity impact tests were carried out under the various room temperatures of −70°C, 70°C, and 140°C. Also, an INSTRON CEAST 9350 drop-tower system has been used to get the impact load, fracture energy, and displacement of the specimens while loading low-velocity impacts. From these tests, the failure pattern, shape, and strength of each test specimen were evaluated for the VAEPC, the PAFRC composite, and the plain mortar. Those test results showed that the flexural strength of both the VAEPC and the PAFRC composites has increased compared to that of the plain mortar. However, the compressive strength of the PAFRC composite decreased slightly after 28 days, while its flexural strength increased by 24.4% compared to that of the plain mortar. In addition, the drop test results show that PAFRC composite specimens have the highest impact fracture energy compared to other specimens at −70°C, 70°C, and 140°C, whereas plain mortar specimens have their lowest. This is because the PVA fiber included in the PAFRC acts as a bridge to suppress crack propagation and to improve energy absorption performance, which helps it resist relatively better against impact. It is also known that while the VAEPC composite and the plain mortar were destroyed in a form of being perforated, the specimens of PAFRC composite were observed to some extent to suppress the perforation failures. Therefore, under a load of low-velocity impact, the resistance performance of the VAEPC composite and the plain mortar was proven to show brittle fracture behavior, while the PAFRC showed ductile fracture behavior in virtue of PVA fiber reinforcement which improved its flexural performance. According to the SEM observation which followed the tests, the PAFRC composite as a fiber-reinforced material of the hydrophilic material was found to show the most excellent interfacial bond adhesion compared to the other composite and the plain mortar. The PAFRC composite manufactured in the study has been proven to be very useful as a reinforcement material in both high and low temperature environments.